Plágio e Universidade: a percepção de acadêmicos do curso de Pedagogia da UFT/Arraias - Ferreira, Thamires Mendes Matos (Universidade Federal do Tocantins, 2020)
This text presents the results of a research carried out in the UFT Pedagogy course, Campus of Arraias, about the use of the text and ideas of the other in academic works. To this end, I was analyzed the comprehension of university students in the conclusion phase of the course about plagiarism in the academic environment. For this work, the research was organized in stages, the first of a theoretical nature, with studies and reflections on authors and research on academic literacy and paraphrase and plagiarism (OLIVEIRA, 2010; ULHOA, 2006; LIMA, 2013; ORLANDI, 2004; BLATTMANN, FRAGOSO, 2003; CHRISTOFE, 1996; BESSA, BERNADINHO, BIRTH, 2012; GARSCHAGEN, 2006; KROKOSCZ, 2011; BARBASTEFANO, SOUZA, 2007; AIRES, 2017). Then, a survey was conducted by applying questionnaires to 36 (thirty-six) university students about their knowledge and impressions about plagiarism in the academic space. From the data collected and the analysis made it was possible to verify that the academics have simple notions about the concept of paraphrase, and that most do not use it properly, still committing the plagiarism forms, and presenting various reasons and justifications for its occurrence.